2021
DOI: 10.3390/ijgi10040235
|View full text |Cite
|
Sign up to set email alerts
|

Linking Public Transport User Satisfaction with Service Accessibility for Sustainable Mobility Planning

Abstract: Increasing the Quality of Service (QoS) of Public Transport (PT), in order to attract more users, is one of the goals of transport companies and urban policy-makers. A continuous monitoring of data on users’ satisfaction is desirable, but most of the time such process is costly. Finding correlations between PT accessibility, user satisfaction and PT ridership might be the key to prioritize where and how service quality improvements have to be put in place. The aim of this paper is to investigate the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 56 publications
0
9
0
2
Order By: Relevance
“…Testing the H3 hypothesis indicates that perceived accessibility as a mediating variable significantly affects satisfaction with travel. In the previous study, Lättman et al (2019) and Inturri et al (2021) showed that perceived accessibility is related to satisfaction with travel. The perceived accessibility captures the individual's experience related to social consequences towards the objective transportation environment.…”
Section: The Effect Of Perceived Accessibility Scale On Satisfaction ...mentioning
confidence: 89%
See 1 more Smart Citation
“…Testing the H3 hypothesis indicates that perceived accessibility as a mediating variable significantly affects satisfaction with travel. In the previous study, Lättman et al (2019) and Inturri et al (2021) showed that perceived accessibility is related to satisfaction with travel. The perceived accessibility captures the individual's experience related to social consequences towards the objective transportation environment.…”
Section: The Effect Of Perceived Accessibility Scale On Satisfaction ...mentioning
confidence: 89%
“…A previous study highlighted that service quality has been important for perceived accessibility in daily travel (Lättman et al, 2016b;Friman et al, 2020). Perceived accessibility has a role in travel satisfaction and general life satisfaction (Lättman et al, 2019;Inturri et al, 2021). It became the mediating role between service quality and satisfaction with travel.…”
Section: Materials and Methods Model Development And Hypothesismentioning
confidence: 98%
“…They found a significant influence of this policy on student behaviour, paving the way for future stages in which continuous monitoring of PT level of service, along with student experience, will be critical to improving PT and promoting a paradigm shift in transportation. Inturri et al [225] used a spatial and statistical method to establish meaningful and easy indicators for sustainable mobility planning by investigating the association between PT usage, user satisfaction, and PT accessibility. Eco-driving is another modern approach that tries to reduce GHG emissions in the existing vehicle infrastructure through efficient fuel use.…”
Section: Approachesmentioning
confidence: 99%
“…Wang et al [9] found that poor accessibility to PT fosters the introduction of DRT services to cover longdistance trips. Besides, accessibility, safety, and comfortrelated indicators should be considered to evaluate the satisfaction of PT users [13][14][15]. Real case studies (or pilots) involving DRT operations have been set up and investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%